Type I Diabetes Mellitus among Children and Adolescent in Sulaimaniyah City, Iraq - Amin, Khelan Saeed Hama; Salih, Karzan Jalal; Ghafoor, Dlzar Dlshad (Sulaimani Journal for Pure and Applied Sciences, 2023)
Diabetes mellitus type I is an autoimmune disorder in which pancreatic β cell autoantibodies are the most significant immunological markers. In this study, we investigated the prevalence of antibodies GADA, IAA, IA2A, and ICA. Seventy-seven patients were selected for the study and another 93 healthy controls were studied. Autoantibodies were measured in the serum samples obtained from both patients and the control group using enzyme-linked immunosorbent assay (ELISA). According to the results of this study, there was a significant difference in the level of GAD65 when the patient group was compared to the control. The mean value for the GAD in the control group was 2.095±0.89, while in patient groups it was 3.56±3.95 ng/ml, and they were significantly different (p<0.01). A qualitative measurement for both antibodies ICA and IA2A showed a positive result in more than 50% of the patients while ICA was positive in 12% of the control groups and IA2A was positive in 1.3% in the control group. Qualitative assessment of the IAA antibodies revealed that 32.8% were positive, while all healthy subjects were negative. Fasting C-peptide level in the patient group was 0.745±0.12 ng/ml while it was 2.12±0.48 ng/ml in healthy subjects. HbA1C level in patients was 10.46±2.27 while it was 5.38±0.24 in healthy subjects. The risk factors, maternal status, and children’s status effect on the development of diabetes were studied and it was found that a significant difference (p<0.05) when a family history of DM was compared with patient and control groups, while there was not significant difference found between both groups when a family history of other autoimmune diseases was compared. Neonatal diseases between both groups were compared and no significant difference was observed as well. From the result of this study, it can be concluded that environmental risk factors such as obesity, family history of DM may play a significant role in triggering the immune system and leading to beta cells destruction, while ethnic background, geography, maternal obesity, maternal diseases, infections during pregnancy, neonatal diseases such as jaundice, thyroid, vitiligo, and celiac are not regarded as a potential risk factor in developing the disease. More than 90% of T1D individuals tested positive for autoantibodies. The most often found autoantibodies were IA2A and GADA. Antibodies were much more prevalent in female children.
Keywords: GADA; ICA; IA2A; IAA; risk factors; TIDM